Effects of activated carbon and cationic exchange resin pretreatments on groundwater defluoridation by reverse osmosis process - Praphasiri Chantharawong (2018)
© 2017, Chulalongkorn University 1. All rights reserved. The objective of this research was to study the effects of a pretreatment using activated carbon and cationic exchange resin on groundwater defluoridation by a reverse osmosis membrane. Actual groundwater containing a high fluoride concentration was collected and examined. Experiments were operated under controlled conditions: a transmembrane pressure of 0.6 MPa and temperature of 25 °C. The reverse osmosis system with activated carbon and cationic exchange resin pretreatments had higher flu oride removal than the one without the pretreatments, 97% compared to 95%, respectively. Additionally, the reverse osmosis system with the pretreatments also produced a higher permeate flux, 1.1×10 -5 compared 9.6×10 -6 m 3 /m 2 ·s without the pretreatment. When the reverse osmosis systems with and without pretreatments were fouled, they showed a decrease in fluoride rejection, as well as a permeate flux decline. After the fouled reverse osmosis membranes were chemically cleaned, the permeate flux recovery and the fluoride rejection of the osmosis system with the pretreatments improved. It could be concluded that the activated carbon and cationic exchange resin played an important role in improving the reverse osmosis system as they contributed to high fluoride rejection and high permeate flux.